Perception of homestay operators towards homestay development in Malaysia - Md Shafiin Shukor,; Norlida Hanim Mohd Salleh,; Redzuan Othman,; Siti Hajar Mohd Idris, (Penerbit Universiti Kebangsaan Malaysia, 2014)
This study aimed to analyse the perception of operators on the impact they experienced as a result of their involvement in the development of homestay. The impacts encompass the economic, social, cultural and environmental aspects. This study employed face to face survey, and a total of 333 respondents who are Peninsular Malaysia’s homestay operators participated in this study. The Structural Equation Modeling (SEM) analysis utilizing simple statistical analysis software with the aid of Statistical Package for the Social Science (SPSS) and Analysis of Moment Structure (AMOS) were employed. Study results indicated that the economic and cultural aspects are significant contributors to the impact experienced by the operators in Malaysia at (0.29, t = 2.78, p < 0.00) and (0.86, t = 6.34, p < 0.00), respectively. Generally, the overall impact has positive relationship and affects the development of homestay tourism (0.30, t = 4.45 p < 0.00). In order to further improve the demand for homestay, there is a need for a strong co-operation between the operators, government and marketing agencies in sustaining Malaysia’s homestay industry development.